Desenvolvimento tecnológico de extratos vegetais padronizados a partir de Brosimum gaudichaudii Trécul (Moraceae) - Martins, Frederico Severino (2012)
Brosimum gaudichaudii Trécul is a species belonging to the Moraceae, It is endemic to the Brazilian savana and is used in the treatment of vitiligo due to the presence of furocoumarins, psoralen and bergapten. This work aimed to the technological development of standardized plant extracts from the roots of B. gaudichaudii. The work began by characterizing the plant drug was obtained and then the liquid extracts (percolation) and dried (spray dryer), with a previous study of process optimization. The optimization study was performed by a 33 factorial design (Box-Behnken), which included the evaluation of factors, extraction time, particle size and alcohol degree. This step revealed that the optimum conditions for extraction of psoralen and bergapten in ultrasound time were 25 min, particle size (150-200µm) and alcohol degree between (55-60%). The extraction by percolation was necessary for 21 days, after which time the biochemical markers were depleted of plant drug. The liquid extract standardized had a density of 0.93 g / ml, 5.41% solids (w / w), pH 6.4 and 22% alcohol degree. The contents of furocoumarins were 1.1% (w / w) of psoralen and 2.94% (w / w) of bergapten. The stability study showed that psoralen and bergapten chemical markers are stable for the stability conditions studied. The spray drying conditions were optimized in the 100 ° C, 5 mL / min and 50%. The drying did not cause loss of psoralen bergapten.